Two Components of the Total Ionization Cross Sections of Atoms and Molecules by Electron Impact: Resonant Excitation and Decay of the Fermi Electron-Hole System and the Dipole Electron Transition from a Bound to a Free State at a Binary Collision - Вайсбурд Д. И. Давид Израйлевич (2003, 2003)
Title screen